Piezo-Active Composites Microgeometry-Sensitivity Relations - Topolov, Vitaly Yu (Springer Series in Materials Science,, 2018)
This book is devoted to the systematic description of the role of microgeometry of modern piezo-active composites in the formation of their piezoelectric sensitivity. In five chapters, the authors analyse kinds of piezoelectric sensitivity for piezo-active composites with specific connectivity patterns and links between the microgeometric feature and piezoelectric response. Among connectivity elements to be discussed, of interest are 2-2, 1-3, 1-1, and 0-3. The role of components and microgeometric factors is discussed in the context of the piezoelectric properties and their anisotropy in the composites. Interrelations between different types of the piezoelectric coefficients are highlighted. The monograph fills a gap in piezoelectric materials science and provides readers with data on the piezoelectric performance of novel composite materials that are suitable for sensor, transducer, hydroacoustic, energy-harvesting, and other applications.